The Porous Veil: A Study On The Influence Of Eec And Us Competition Law On Australian Trade Practices Law - Khoo, Eugene (Journal of Malaysian and Comparative Law, 2019)
Australia shares with Western Europe and the United States of America a common political and economic heritage. In the economic sphere this includes the belief that competition in the market place is the best means by which the sources of production can best be chanelled and utilised - ultimately leading to an increase in consumer welfare. This paper seeks to examine the influence of the competition laws of the European Economic Community (EEC) and the antitrust laws of the United States of America (US) on Australian trade practices laws.